Public Awareness and Preventive Practices Regarding Gastrointestinal Non-Communicable Diseases (NCDs) in Rural Pakistan: A Community-Based Study - Muhammad Tauseef Javed, Sheema Khan, Ghulam Shabir Shaikh, Bilal Masood, Abdul Wadood Shah, Ghulam Hussain Baloch, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gastrointestinal non-communicable diseases (GI-NCDs) such as chronic liver disease, gastrointestinal cancers, and inflammatory bowel diseases are an emerging public health concern in Pakistan, particularly in rural areas where awareness and preventive practices are poorly documented. Objective: To assess public awareness and preventive practices regarding GI-NCDs among rural populations in the catchment areas of Gujranwala Medical College Teaching Hospital (GMCTH), Gujranwala, and Khyber Teaching Hospital (KTH), Peshawar. Methods: This community-based cross-sectional study was conducted from January 2022 to January 2023 on 200 adult participants (100 from each district) selected through multistage sampling. Data were collected using a structured, pre-tested questionnaire covering socio-demographics, knowledge, risk factor awareness, and preventive practices. Analysis was performed using SPSS version 26.0, with associations tested using the Chi-square method at a significance level of p<0.05. Results: The mean age of participants was 39.6 ± 12.8 years, with 54.5% females and 65.5% having no formal or only primary education. Correct identification of GI-NCD examples was reported by 34.5% of respondents, and awareness of key symptoms varied from 15.0% (rectal bleeding) to 61.0% (abdominal pain). Preventive practices were suboptimal; 72.0% treated drinking water, 41.0% practiced regular hand washing with soap, 20.5% consumed adequate fruits/vegetables, and only 4.5% had ever undergone GI cancer screening. Education level was significantly associated with awareness scores (p<0.001). Conclusion: Public awareness and preventive practices regarding GI-NCDs in rural Pakistan are inadequate. Integrating targeted education, preventive interventions, and accessible screening into rural health programs is essential to reduce the future burden of these diseases. Keywords: Gastrointestinal non-communicable diseases, Public awareness, Preventive practices, Rural health, Pakistan.